An investigation into the extent of, and reason for, the theory-to-practice disparity in Montessori early childhood settings in South Africa - Susanne van Niekerk (Problemy Wczesnej Edukacji)
This mixed methods study investigates the factors that affect the implementation of what is perceived to be “authentic” Montessori practice in South African Montessori preschools through the lived experience of eight teachers trained by Montessori Centre South Africa (MCSA). Previous Montessori research in Europe and North America has addressed the results of, but not the reasons for, modification to Montessori best practice. No research of this kind has to date been conducted in South Africa, which has a substantial Montessori following. This phenomenological study was conducted over a two-month period with eight purposefully selected MCSA graduates from diverse Montessori preschools in Cape Town, Durban, Johannesburg, and Pretoria to explore their lived experiences and to probe for constraints that affect implementation fidelity. Participants completed an online questionnaire which was followed up by extensive individual interviews. Data analysis showed that the majority of the participants experienced situational constraints from school management, parent pressure, and statutory requirements, while some instances of personal bias and reservation towards the Montessori method were also noted. The study’s conclusions highlight the necessity for Montessori teacher training colleges in South Africa to collaborate with the South African Montessori Association and the Montessori preschool owners to uphold the fundamental principles of Montessori best practice to preserve the educational ethos of the Montessori method for the ultimate benefit of the child.